PENYELENGGARAAN OTONOMI DAERAH DI KABUPATEN MERAUKE DENGAN MENGGUNAKAN PRINSIP DESENTRALISASI MELALUI UU NOMOR 32 TAHUN 2004 - Ruloff Fabian Yohanis Waas (Universitas Musamus, Merauke, Papua, 2014)
As the principle of local autonomy means respecting life according to regional history, culture and nature of their own, in a unitary state levels. Each area has a historical and special properties different from the history and nature of the other areas. As an illustration, the Merauke district government perposif selected for empirical legal research, with the consideration that the administration of Merauke district is one of the regional governments have accrued, functions and roles that align with other regional governments, in the ranks of government and system of the unitary Republic of Indonesia. Therefore this paper is a scientific research in the field of law, the method used is the method of legal research.Type of research is qualitative-descriptive legal research using the analytical approach legislation (statute approach) is to examine and analyze several laws relating to the topic and relevant to the issues to be investigated. Broadly speaking, the Act No. 32 of 2004 regulates more detail or details concerning the authority of each area to take care of their own region, as stated in the rationale of Law 32 of 2004 on Local Government which local authorities are expected to further improve the efficiency and effectiveness implementation of regional autonomy.